Sistem Rapor Online di Madrasah Tsanawiyah Al Mumtaz Berbasis Web - Maimanah, Khamidah Toriq; Unggara, Ilham (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2025)
The rapid advancement of information technology has encouraged companies and institutions to enhance data management more effectively and efficiently to support productivity. The online report card system at MTs Al Mumtaz is designed to manage student grades digitally. Currently, grade processing at MTs Al Mumtaz is still done manually using Microsoft Excel, without a specialized application. With a web-based system, it is expected that grade management will improve, allowing students and parents easy access to grades, while also simplifying data entry for teachers, making the process more efficient. This research uses the Waterfall method, with UML, PHP, MySQL, and the CodeIgniter (CI) framework as tools. The results show that the developed online report card system can enhance efficiency in grade management, reduce the risk of data entry errors, and speed up delivering grade information to students and parents. Additionally, the system facilitates teachers in managing grades, both in terms of data entry and final grade processing. The author recommends further development of this system, with additional features such as automatic notifications and mobile application integration, making user access easier and the report card system more optimized.